Cloud Accounting Utilisation and SME Performance in Bali, Indonesia: An Integrated TAM, IS Success, and Contingency Theory Perspective - I Nyoman Sunarta; Partiwi Dwi Astuti; I Made Sudiksa; Ni Kadek Trisnadewi (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study examines how cloud accounting utilisation improves the performance of small and medium-sized enterprises (SMEs) in Bali, Indonesia, by integrating the Technology Acceptance Model (TAM), the DeLone and McLean Information Systems Success Model, and contingency theory. Prior studies have generally examined cloud accounting adoption or business performance separately, leaving limited evidence on how technology acceptance and information-system quality jointly explain cloud accounting use and its performance consequences in emerging-economy SMEs. Using a quantitative survey of 198 SMEs and Partial Least Squares Structural Equation Modelling (PLS-SEM) with WarpPLS 8.0, this study tests the effects of perceived usefulness, perceived ease of use, information quality, system quality, and service quality on cloud accounting utilisation and subsequently on SME performance. The results show that all five antecedents positively and significantly influence cloud accounting utilisation, with system quality and perceived usefulness showing the strongest effects. Cloud accounting utilisation also has a strong positive effect on SME performance. The model explains 78% of the variance in cloud accounting utilisation and 59% of the variance in SME performance. The study contributes by showing that TAM explains user acceptance, the IS Success Model explains system-related drivers, and contingency theory clarifies why cloud accounting creates performance value in a competitive SME context. Practically, SME managers, software vendors, and policymakers should prioritise reliable systems, clear user benefits, responsive support, and digital accounting capability-building. The study is limited by its cross-sectional and self-reported design, suggesting the need for future longitudinal and multi-region research.